2017
DOI: 10.1155/2017/8465125
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association ofMMP10,MMP14, andMMP16with Dental Caries

Abstract: Matrix metalloproteinases (MMPs), which degrade extracellular proteins as part of a variety of physiological processes, and their inhibitors have been implicated in the dental caries process. Here we investigated 28 genetic variants spanning the MMP10, MMP14, and MMP16 genes to detect association with dental caries experience in 13 age- and race-stratified (n = 3,587) samples from 6 parent studies. Analyses were performed separately for each sample, and results were combined across samples by meta-analysis. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…A similar genome‐wide association study investigating clusters of pit‐and‐fissure and smooth surface dental caries in the primary dentition did not identify any significant signals . Additional loci not meeting genome‐wide significance criteria but with multiple lines of supporting evidence requiring some attention, include MMP16 (rs2046315 and rs10429371), PKD2 (rs17013735, rs11938025, rs2725270) and SIBLING (rs2725233), MPPED2 and ACTN2, and TRAV4 . Although additional insights have been gained by gene set enrichment re‐analyses of a dental caries genome‐wide association study reported by Wang et al, the recent, large‐scale consortium meta‐analysis that included clinical and self‐reported data (including denture use) among half a million individuals, discovered 47 novel loci for adult dental caries …”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Dental Diseasementioning
confidence: 98%
“…A similar genome‐wide association study investigating clusters of pit‐and‐fissure and smooth surface dental caries in the primary dentition did not identify any significant signals . Additional loci not meeting genome‐wide significance criteria but with multiple lines of supporting evidence requiring some attention, include MMP16 (rs2046315 and rs10429371), PKD2 (rs17013735, rs11938025, rs2725270) and SIBLING (rs2725233), MPPED2 and ACTN2, and TRAV4 . Although additional insights have been gained by gene set enrichment re‐analyses of a dental caries genome‐wide association study reported by Wang et al, the recent, large‐scale consortium meta‐analysis that included clinical and self‐reported data (including denture use) among half a million individuals, discovered 47 novel loci for adult dental caries …”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Dental Diseasementioning
confidence: 98%
“…The first linkage studies in caries were performed in 2008 [ 32 ] and the first genome-wide association studies for early childhood caries were published in 2011 [ 33 ]. Abbasoğlu et al [ 10 ] were the first to correlate environmental and genetic factors in ECC in Turkish 2–5-year-olds, while Lewis et al [ 34 ] considered several single nucleotide polymorphisms, however they were not included in the final caries prediction meta-analysis. Another technical obstacle in any caries prediction model implementation in practice is an almost total lack of replication and validation studies in independent populations [ 13 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) play an important role in early tooth development by regulating ameloblast maturation and formation of enamel. Several types of MMPs have been described to be involved in dentin collagen degradation and dental caries lesion progression [ 12 , 34 , 39 , 40 , 41 , 42 ]. MMP16 rs10429371 was previously associated with caries in white adults [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of SNP MMP16 rs10429371, C allele was more frequent in RAS patients than in controls and CC + CT genotype carriers of this studied polymorphism had marginally significantly associated higher risk of developing RAS in comparison with TT homozygotes in our population. Intragenic polymorphisms rs10429371 is located upstream of MMP16 and receptor‐interacting serine‐threonine kinase 2 ( RIKP2 or RIP2 ) genes and it has not been elucidated yet, whether this variant has an impact on the expression of either MMP16 or RIPK2 . Regarding the development of RAS, the membrane‐type MMP16 (or MT3‐MMP) is involved in extracellular matrix remodelation, since its substrates include type III collagen, gelatin, or fibronectin .…”
Section: Discussionmentioning
confidence: 99%